1999
DOI: 10.1046/j.1365-2648.1999.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional nurse autonomy: concept analysis and application to nursing education

Abstract: Professional nurse autonomy, an essential attribute of a discipline striving for full professional status, is often confused with personal autonomy, work autonomy or aggregate professional autonomy. Using Walker & Avant's (1995) model for concept analysis, this paper presents an analysis of professional nurse autonomy. Professional nurse autonomy is defined as belief in the centrality of the client when making responsible discretionary decisions, both independently and interdependently, that reflect advocacy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 38 publications
(75 reference statements)
1
109
0
11
Order By: Relevance
“…[30] Uzun yıl-lar boyunca hemşirelik mesleği profesyonellik için çaba gös-termektedir. [31] Temel eğitimde kazanılan bilgi, mesleki otonominin temelini oluşturur. Hemşire hasta bakımında klinik yargılama ve karar vermede mesleki bilgisini kullanır.…”
Section: Otonomiunclassified
“…[30] Uzun yıl-lar boyunca hemşirelik mesleği profesyonellik için çaba gös-termektedir. [31] Temel eğitimde kazanılan bilgi, mesleki otonominin temelini oluşturur. Hemşire hasta bakımında klinik yargılama ve karar vermede mesleki bilgisini kullanır.…”
Section: Otonomiunclassified
“…This questionnaire included closed response questions and Likert-type five response level questions (5. very satisfied, 4. satisfied, 3. moderately satisfied, 2. dissatisfied, 1. very dissatisfied). This tool, created from theinstruments "Measure of Job Satisfaction" (MJS) [25] and "Job Descriptive Index" (JDI) [26] was validated on a sample of 937 care providers who worked in reproductive health facilities inMali and Senegal. It has been shown to have good validity and satisfactory reliability [22].…”
Section: Methodsmentioning
confidence: 99%
“…Acceptance of one another and collaboration of ideas has been shown to better outcomes of patient care. Studies also showed that interdependence with members of the healthcare team help develop nurse autonomy [20].…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
“…"Interdependence stimulates and challenges individual opinion, guides and augments initiative, and demands individual responsibility and accountability, attributes strongly associated with professional nurse autonomy, " which pertained to character and belief in oneself (para. 13) [20]. Teamworkwas conveyed as being vitalfor systems to work interdependently based on faith and acceptance of the members' character and competence.…”
Section: Antecedents and Consequencesmentioning
confidence: 99%